The Scholars’ Perceptions of Integrating Popular Culture into Academic Speaking and Writing - Wijirahayu, Suciana; Ananda, Shifa; Ringo, Narina; Yunus, Galih Aprinanda; Sari, Yessy Yanita (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research explores the impact of integrating popular culture elements such as music, film, and social media on language acquisition and overall student learning. Through surveys and questionnaires, the study examines students' perceptions of pop culture's role in their educational journey. A survey was conducted with 36 pre-service teachers at a private university in Jakarta to support this research. A descriptive statistical analysis of the data is conducted to identify trends and patterns in learner experiences.This study argues that popular culture, with its wealth of authentic materials, can serve as a valuable tool for effective teaching and learning for pre-service teachers in the EFL context. While recognizing the potential benefits of increased engagement and cultural understanding, the research also addresses challenges like limited vocabulary exposure and the need for careful material selection. Ultimately, this study aims to promote the effective integration of popular culture into EFL Academic Speaking and Writing classrooms by identifying best practices and addressing the diverse needs of learners. The findings of this study have the potential to further motivate pre-service teachers to engage in English language teaching and learning, as well as enhance their communicative and socio-cultural competence.